Paleoenvironmental reconstruction of the semi-arid Chaco region of Argentina based on multiproxy lake records over the last six hundred years - Speranza, Flavio Cesar; Giralt, Santiago; Concepción Lupo, Liliana; Kulemeyer, Julio José; Pereira, Elizabeth de los Ángeles; Claramunt López, Bernat (Elsevier, 2019)
In this paper, we analyze the paleoclimatic and paleoenvironmental evolution of Laguna Yema in semi-arid Chaco region of Argentina over the past six hundred years. High resolution multiproxy studies of lake sediments utilize analyses of lithology, mineralogy, geochemistry, palynology, and are constrained by radiocarbon and gamma spectrometry dating. Laguna Yema sediments were mainly composed of well stratified fine sediments (silts and clays), with variable proportions of quartz, clays (illite) and feldspar (microcline and albite). Twelve light and heavy geochemical elements were registered. Most elements (Al, Si, K, Ti, Fe, Rb, Ba, and Br) are associated with illite and albite. Different material transport processes related to the changes in aridity and humidity of the basin were identified using the main mineralogical origins of geochemical elements. Palynological records indicate cycles of contraction and expansion of the lake, with an increase in concentration of Alternanthera aquatica during wet periods (expansion of lake), and an increase in Ambrosia, Poaceae and fern spores during dry periods (contraction of lake). These changes are linked to fluctuations in moisture conditions in the Subandean Mountains and semi-arid Chaco regions, in response to interactions between the South American Monsoon System (SAMS) and the South American Low Level Jet (SALLJ), which send warm and humid air to northern Argentina. In a regional context, the Laguna Yema records are in accordance with the analyses of the temporal and spatial pattern of moisture distribution for the last six centuries.